The Effect of Brand Image and Product Quality toward Wardah Cosmetics Consumers’ Loyalty as A Study on Students Management Study Program, Faculty of Econom ics and Business, Muhammadiyah University of Bengkulu - Liana Sapitri; Onsardi Onsardi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study almed to determine the effect of brand image and product quality toward Wardah Cosmetics Costumers’ loyalty as the study on Students of Management Study Program, Faculty Economics and Business, Muhammadiyah University of Bengkulu. The data collection technique of this study used observation, interviw, and quetionnaire. The data analysis technique of this study used instrument tests, classical assumption tests, analysis of respondents’ respones, multiple linier analysis of the determination coefficient and also hypotesis testing. The result of the study show that in line with the multiple linier test obtained the regression equation which is as follows: Y= 5.224 + 0.200 (X_1) + 0.332 (X2). The test result can be seen that the variable Brand Image (X1) show tcount> ttable (2.502 > 1.98580) and (sig <α = 0,014 < 0.050) variable Product Quality (X2) obtained tcount> ttable (9.150 > 1.98580) and (sig <α = 0,000 < 0.050). Based on the finding above can be concluded that Brand Image and Product Quality have a positive and significant effect toward Wardah Cosmetics Costumers’ Loyalty as a study on students of Management Study Program, Faculty of Economics and Business, Muhammadiyah University of Bengkulu.